Elaboração de snacks a partir da mistura de polpa e casca de graviola desidratados - Gomes, Lara Carolina Gonçalves (2019)
Increased food consumption and excess waste have aroused interest in the full utilization of food, and drying operations can provide conditions for better utilization of all its parts. Such operations promote the reduction of the water activity and the moisture of a product, allowing the increase of its shelf life, and therefore have been applied to fruits. Soursop, a tropical fruit with characteristic flavor and aroma and high nutritional value, is harvested in only three months of harvest, indicating a high potential for better utilization through drying operations. Thus, this study aimed to develop snacks formulated from a flour, obtained from the mixture of pulp and soursop bark, dried by three different methods: freeze-drying, foam-mat and microwave, the latter in the powers of 200, 280 and 480 W. Flours with satisfactory final moisture levels below 15% were obtained by the different methods. The use of the microwave in the power of 480W stood out as the most efficient, among those studied, in relation to the drying time, although the appearance of the flour did not meet the desired sensorial criteria. The drying operation that best kept the physical-chemical characteristics in the final product, compared to the in natura, was the freeze-drying, however, the flour obtained by microwave in the power of 200W was the one that presented higher values of bioactive compounds, therefore, selected, together with the freeze-dried and foam-mat dried flours, for the formulation of the snacks. After the elaboration, they were submitted to physical-chemical analysis, presenting difference mainly in relation to the staining, and the sensorial evaluation, through acceptance test and preference sorting test, allowed to conclude that the product elaborated with flour obtained by foam bed was the one that presented greater acceptance and preference. The centesimal composition of the snacks elaborated with the flour obtained by the three drying methods presented close values for the formulations, mainly in relation to the protein and lipids content. It can be concluded that the drying operation is feasible to obtain the flour, and that this can be applied in several products, among them the snacks.